New insights into the recent collapse of Eastern Baltic cod from historical data on stock health - Margit Eero; Keith Brander; Tatjana Baranova; Uwe Krumme; Krzysztof Radtke; Jane W. Behrens (PLoS ONE, 2023)
The Eastern Baltic cod (Gadus morhua) stock is currently in a very poor state, with low biomass and adverse trends in several life history and demographic parameters. This raises concern over whether and to what level recovery is possible. Here, we look for new insights from a historical perspective, extending the time series of various stock health indicators back to the 1940s, i.e. to the beginning of intensive exploitation of the Eastern Baltic cod. The historical data confirm that the stock deterioration in recent years is unprecedented, as all indicators are presently in their worst states on record. Cod body condition and energy reserves were equally low in the 1940s–1950s, accompanied by high parasitic liver worm infection, comparable to that measured in recent years. However, other stock parameters (size structure, size at maturity, stock distribution) are currently in their worst states over the past 80 years. In contrast, the state of cod in the 1970s to early 1990s that is often perceived as a desirable target, was exceptional, with the most favorable indicator levels in the time series. Long-term observation data reveal concurrent or asynchronous trends in different indicators of stock health and to what extent these have coincided with changes in possible external drivers. In this way, the extended time series contribute to ongoing research on understanding the collapse of the cod and its recovery potential.